Grid-tied photovoltaic and battery storage systems with Malaysian electricity tariff - A review on maximum demand shaving - Subramani G.; Ramachandaramurthy V.K.; Padmanaban S.; Mihet-Popa L.; Blaabjerg F.; Guerrero J.M. (MDPI AG, 2023)
Electric batteries; Energy policy; Energy utilization; Investments; Sales; Solar power generation; Battery storage system; Electricity tariff; Maximum demand; Net metering; Peak shaving; Photovoltaic; Battery storage